(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
During the second spanish liberal experience, the press played a crucial role as a space for analysis, discussion, debate, and controversy that simmered in the highest spheres of power, including the complex and ever-changing issue of American dissent and the desired independence. The prominence of both public opinion and public debate was evident. In this tumultuous context of mid-1821, the development of political journalism as a groundbreaking revelation contributed to the formation of identities and the construction of political life in both Spain and America. This article highlights the public debate on the pacification of America and the paths that should be forged for a post-independence relationship, although the focus is particularly on the revered New Spain, a perennial concern in this conflict. The participating columnists freely expressed their opinions and offered solutions to the sensitive problem under discussion, exerting an unavoidable influence on public opinion and generating debates on how to put an end to the bloody effusion that had overshadowed the region for over a decade. At least within a sector of Spanish society, there was hope of finding a path towards lasting peace and a promising future for the Spanish territories on both sides of the Atlantic.